Range‐wide population structure of European sea bass Dicentrarchus labrax. (26th May 2015) - Souche, Erika L.; Hellemans, Bart; Babbucci, Massimiliano; MacAoidh, Eoin; Guinand, Bruno; Bargelloni, Luca; Chistiakov, Dimitry A.; Patarnello, Tomaso; Bonhomme, François; Martinsohn, Jann T.; Volckaert, Filip A. M.
<x xml:space="preserve">Abstract</x> The euryhaline European sea bass Dicentrarchus labrax L., inhabiting the coasts of the eastern Atlantic Ocean and Mediterranean Sea, has had many opportunities for differentiation throughout its large natural range. However, evidence for this has been incompletely documented geographically and with an insufficient number of markers. Therefore, its full range was sampled at 22 sites and individuals were genotyped with a suite of mapped markers, including 14 microsatellite loci (N = 536) and 46 neutral or gene‐linked single nucleotide polymorphisms (SNPs; N = 644). We confirm that the Atlantic and Mediterranean basins harbour two distinct lineages. Within the Atlantic Ocean no pattern was obvious based on the microsatellite and SNP genotypes, except for a subtle difference between South‐eastern and North‐eastern Atlantic sea bass attributed to limited introgression of alleles of Mediterranean origin. SNP genotypes of the Mediterranean lineage differentiated into three groups, probably under the influence of geographical isolation. The Western Mediterranean group showed genetic homogeneity without evidence for outlier loci. The Adriatic group appeared as a distinct unit. The Eastern Mediterranean group showed a longitudinal gradient of genotypes and most interestingly an outlier locus linked to the somatolactin gene. Overall, the spatial pattern fits those observed with other taxa of between‐basin segregation and within‐basin connectivity, which concurs well with the swimming capabilities of European sea bass. Evidence from a few outlier loci in this and other studies encourages further exploration of its regional connectivity and adaptive evolution.